Searching for GEMS: Two Super-Jupiters Around M Dwarfs that May have Formed via Gravitational Instability - Andrew Hotnisky; Shubham Kanodia; Jessica Libby-Roberts; Suvrath Mahadevan; Caleb I. Cañas; Arvind F. Gupta; Te Han; Henry A. Kobulnicky; Alexander Larsen; Paul Robertson; Michael Rodruck; Gudmundur Stefansson; et al. (The Astronomical Journal)
We present the discovery of TOI-6303b and TOI-6330b, two massive transiting super-Jupiters orbiting a M0 and a M2 dwarf star, respectively, as part of the Searching for Giant Exoplanets around M-dwarf Stars (GEMS) survey. These were detected by NASA’s Transiting Exoplanet Survey Satellite and then confirmed via ground-based photometry and radial velocity observations with the Habitable-zone Planet Finder. TOI-6303b has a mass of 7.84 ± 0.31 M _J , a radius of 1.03 ± 0.06 R _J , and an orbital period of 9.485 days. TOI-6330b has a mass of 10.00 ± 0.31 M _J , a radius of 0.97 ± 0.03 R _J , and an orbital period of 6.850 days. We put these planets in the context of super-Jupiters around M dwarfs discovered from radial-velocity surveys, as well as recent discoveries from astrometry. These planets have masses that can be attributed to two dominant planet formation mechanisms—gravitational instability and core accretion. Their masses necessitate massive protoplanetary disks that should either be gravitationally unstable, i.e., forming through gravitational instability, or be among the most massive protoplanetary disks known to date to form objects through core accretion. We also discuss their possible migration mechanisms via their eccentricity distribution.